Devilishly radical NETwork in COVID-19: Oxidative stress, neutrophil extracellular traps (NETs), and T cell suppression - Schönrich, Günther; Raftery, Martin J.; Samstag, Yvonne (Advances in Biological Regulation, 2020)
Pandemic coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and poses an unprecedented challenge to healthcare systems due to the lack of a vaccine and specific treatment options. Accordingly, there is an urgent need to understand precisely the pathogenic mechanisms underlying this multifaceted disease. There is increasing evidence that the immune system reacts insufficiently to SARS-CoV-2 and thus contributes to organ damage and to lethality. In this review, we suggest that the overwhelming production of reactive oxygen species (ROS) resulting in oxidative stress is a major cause of local or systemic tissue damage that leads to severe COVID-19. It increases the formation of neutrophil extracellular traps (NETs) and suppresses the adaptive arm of the immune system, i.e. T cells that are necessary to kill virus-infected cells. This creates a vicious cycle that prevents a specific immune response against SARS-CoV-2. The key role of oxidative stress in the pathogenesis of severe COVID-19 implies that therapeutic counterbalancing of ROS by antioxidants such as vitamin C or NAC and/or by antagonizing ROS production by cells of the mononuclear phagocyte system (MPS) and neutrophil granulocytes and/or by blocking of TNF-α can prevent COVID-19 from becoming severe. Controlled clinical trials and preclinical models of COVID-19 are needed to evaluate this hypothesis.